(untitled) (Proceedings of Southern Federal University. Philology, 2020)
communication between the national and ethnic minorities, and the majority of the population is impossible. However, today’s mass media connect these two social groups through the Internet and provide a platform to exchange their views online. Modern «dialogue» through the online mass media is possible with the help of interviews with minorities. Online media provide a platform for communication of different segments of the population by organizing a dialogue between representatives of different cultures. This study aims to evaluate the possibility of such a «dialogue», and its implementation in the online version of the newspaper «Le Monde». We believe that the media, being in a position to create a space for the dialogue between minority and majority, have a significant influence on the content produced by selecting quotes, articles for publication, and conducting interviews within the given topic, avoiding any derogation. During the time of terrorist attacks in Europe in 2015-2016, the voice of the French Muslim minority and migrants living in the country was expected to be heard. One of the most visited French websites lemonde.fr did not provide the significant opportunity to speak to these categories of citizens, limiting their opinions by official representatives’ statements. Key words: dialogue, intercultural communication, minorities, public sphere, media effects, public opinion. DOI 10.18522/1995-0640-2020-1-218-226